Utilização de serviços de média e alta complexidade em hospitais de referência na maior fronteira internacional do Brasil - Alliana, Fernanda da Silva Pumi (2021)
To verify whether the use of medium and high complexity health services in Brazilian reference hospitals in a trinational border region is due to non-overload of the system. Methods: Analytical study with a quantitative observational approach carried out with data related to medium and high complexity care in two reference hospitals in the city of Foz do Iguaçu, Paraná, located in the region of the Trinational Border Brazil- ParaguayArgentina. Data referring to medium and high complexity services provided from 2015 to 2018 were forwarded. The frequencies of procedures and hospitalizations of three groups of users were compared: those from the 9th Regional Health of Paraná (9RS), those from other Brazilian health regions (BRA) and residents not abroad (Brazilians or foreigners, EXT). Use Fisher’s test with Monte Carlo algorithm with 99% confidence and 10,000 to compare how frequencies of procedures of user groups (9RS, BRA and EXT). The V for Cramér was established to represent a strength of the observed association. Results: During the study period, 340,701 procedures. The consultations performed in the 9RS group accounted for 97.0% (330,444) procedures, while those in the BRA group accounted for 2.8% (9,641) procedures and EXT accounted for 0.2% (616) procedures. Regarding the number of admissions, there was a total of 282,644 admissions, 24.4% (69,092) of the total performed in the Hospital Ministro Costa Cavalcanti, and 75.6% (213,552) of the total performed in the Hospital Municipal Padre Germano Lauck. Regarding the year with the highest use of health services, the year 2015 had the highest total number of procedures, approximately 34.9% (98,576). Final Considerations: Non-resident users use a small fraction of medium and high complexity health services in Brazilian reference hospitals in the border region, and it is apparently inappropriate to claim that they are overloaded with medium and high complexity hospital services in these regions.